THE ROLE OF MOTHER TONGUE-BASED MULTILINGUAL EDUCATION IN ENHANCING EXECUTIVE FUNCTIONS IN BALINESE CHILDREN - Jean Dupont; Marie Müller; Pierre Lenz (International Journal of Educatio Elementaria and Psychologia, 2025)
This study investigates the role of Mother Tongue-Based Multilingual Education (MTB-MLE) in enhancing executive functions among Balinese primary school children. The research stems from the growing recognition that early bilingual and multilingual experiences influence cognitive control, working memory, and attentional flexibility. The study aims to determine how instruction that integrates Balinese, Indonesian, and English affects children’s cognitive development, particularly their executive functioning skills. Using a mixed-methods design, data were collected from 120 students across three primary schools implementing MTB-MLE programs. Quantitative assessments of inhibitory control, cognitive flexibility, and working memory were complemented by qualitative classroom observations and teacher interviews. The findings revealed that children educated under MTB-MLE demonstrated significantly higher performance in attention-shifting and problem-solving tasks compared to peers in monolingual instruction. Qualitative data supported that the use of the mother tongue enhanced comprehension, participation, and self-regulation. These results suggest that multilingual education not only preserves linguistic and cultural identity but also strengthens cognitive adaptability essential for academic success. It concludes that policy support for MTB-MLE in early education can contribute to both linguistic equity and neurocognitive development in multilingual societies.